READING, COMPUTER AND HEALTH - A.A. Baranov; V.R. Kuchma; L.M. Teksheva (Вопросы современной педиатрии, 2008)
The wide use of computer information media in education process and children and teenagers' leisure activities set new tasks for hygienists and physiologists in assessment of the influence of computer lessons on health, as well as in substantiation and development of ways of formatting and presenting materials from the viewpoint of legibility and regulation of teaching modes. In this work, data related to the study of response of students' optical system depending on the ways of presenting the information (on a screen or on a paper medium), assessment of functional status of children and teenagers after computer classes, are presented, analysis and assessment of modern electronic tutorials are given.Key words: children, reading, computers, electronic tutorials, health.